ILLOCUTIONARY ACTS OF SENT AND UNSENT MESSAGES VIA PERSONAL MESSAGES AND GROUP CHATS - Mark Philippe S Guyud (Leksema: Jurnal Bahasa dan Sastra, 2022)
New features of communication technology are gaining much attention in computer-mediated communication in relation to speech acts and conversational implicatures which aim to transcend the conventional and nonconventional meaning of words, phrases, or sentences when an interlocutor conveys messages in varied contexts. By examining 30 exchanges and conducting survey interviews, this study concerns the illocutionary acts of sent and unsent messages both in personal messages and group chats via an online messaging application. The findings show that there are 7 identified meanings of unsent messages; moreover, although there are similarities, the meaning varies depending on the context. The study also shows that students use representatives more frequently than the other illocutionary acts in sent messages both in personal and group chats. It is also noteworthy to point out that students rarely use greeting speech acts in their messages.